Poor Outcomes in Kidney Transplant Candidates and Recipients With History of Falls. Issue 8 (August 2020) - Chu, Nadia M.; Shi, Zhan; Berkowitz, Rachel; Haugen, Christine E.; Garonzik-Wang, Jacqueline; Norman, Silas P.; Humbyrd, Casey; Segev, Dorry L.; McAdams-DeMarco, Mara A.
Abstract : Background: Falls occur in 28% of hemodialysis patients and increase the risk of physical impairment, morbidity, and mortality. Therefore, it is likely that kidney transplantation (KT) candidates with recurrent falls are less likely to access KT and more likely to experience adverse post-KT outcomes. Methods: We used a 2-center cohort study of KT candidates (n = 3666) and recipients (n = 770) (January 2009 to January 2018). Among candidates, we estimated time to listing, waitlist mortality, and transplant rate by recurrent falls (≥2 falls) before evaluation using adjusted regression. Among KT recipients, we estimated risk of mortality, graft loss, and length of stay by recurrent falls before KT using adjusted regression. Results: Candidates with recurrent falls (6.5%) had a lower chance of listing (adjusted hazard ratio [aHR] = 0.68, 95% confidence interval [CI], 0.56-0.83) but not transplant rate; waitlist mortality was 31-fold (95% CI, 11.33-85.93) higher in the first year and gradually decreased over time. Recipients with recurrent falls (5.1%) were at increased risk of mortality (aHR = 51.43, 95% CI, 16.00-165.43) and graft loss (aHR = 33.57, 95% CI, 11.25-100.21) in the first year, which declined over time, and a longer length of stay (adjusted relative ratio [aRR] = 1.13, 95% CI, 1.03-1.25). In summary, 6.5% of KT candidates and 5.1% of recipients experienced recurrent falls which were associated with adverse pre- and post-KT outcomes. Conclusions: While recurrent falls were relatively rare in KT candidates and recipients, they were associated with adverse outcomes. Transplant centers should consider employing fall prevention strategies for high-risk candidates as part of comprehensive prehabilitation.